A comparison of glacial and paraglacial denudation responses to rapid glacial retreat. Issue 80 (December 2019) - Williams, Haley B.; Koppes, Michele N.
Abstract: Glacier thinning and retreat drives initial acceleration of glacier sliding and erosion, de-buttressing of steep valley walls, and destabilization of ice-marginal deposits and bedrock, which can lead to massive rock avalanching and accelerated incision of tributary watersheds. A compelling example of these changes occurred in Taan Fjord in SE Alaska due to the rapid thinning and retreat of Tyndall Glacier over the past half century. Increased glacier sliding speeds led to both increased rates of subglacial erosion and the evacuation of subglacially stored sediments into the proglacial basins. The shrinking glacier also exposed proglacial tributary watersheds to rapid incision and denudation driven by >350 m of baselevel fall in a few decades. Moreover, in October 2015 a large tsunamigenic landslide occurred at the terminus of Tyndall Glacier, largely due to thinning exposing oversteepened, unstable slopes. Sediment yields from the glacier, the landslide and the tributary watersheds, measured from surveys of the sediments in the fjord collected in 1999 and 2016, are compared to ongoing changes in glacier and fjord geometry to investigate the magnitude of glacial and paraglacial denudation in Taan Fjord during retreat. In the last 50 years, sediment yields from the glacier and non-glacial tributaries kept pace with the rapid rate of retreat, and were on par with each other. Notably, basin-averaged erosion rates from the paraglacial landscape were twice that from the glacier, averaging 58 ± 9 and 26 ± 5 mm a −1, respectively. The sharp increases in sediment yields during retreat observed from both the glacier and the adjacent watersheds, including the landslide, highlight the rapid evolution of landscapes undergoing glacier shrinkage.